Pengelolaan Barang Milik Daerah Berdasarkan Peraturan Pemerintah Nomor 27 Tahun 2014 tentang Pengelolaan Barang Milik Negara/Daerah - Febriana, Era Nandya; Jayus, Jayus; Indrayati, Rosita (University of Jember, 2017)
Indonesia is the Unitary State. It is understood that within a unitary state, the central government operates a high state sovereignty. In order not to be arbitrary, the activities of the central government are supervised and limited by the constitution. The government which is divided from the Central Government to the Regional Government included Regional Autonomy therein, as well as the authority of the Regional Government, is on duty to manage the Regional Property. In carrying out its authority as an administrator of local property, there are still many abuses or omissions committed by the local government in operating its authority in managing regional property, such as the negligence of the Regional Assets, the misuse of authority in the revocation of rights already granted by the regional government on the right to use of local property, using local property for personal interest. In the management of regional property required planning, implementation, and supervision by the local government in accordance with applicable laws and regulations in the constitution. Keywords: Authority, Local Government, Management of Regional Property